Structure based design, synthesis, and evaluation of anti-CML activity of the quinolinequinones as LY83583 analogs. (25th August 2021) - Bayrak, Nilüfer; Ciftci, Halil I.; Yıldız, Mahmut; Yıldırım, Hatice; Sever, Belgin; Tateishi, Hiroshi; Otsuka, Masami; Fujita, Mikako; Tuyun, Amaç Fatih
Abstract: Quinone-based small molecules are the promising structures for antiproliferative drug design and can induce apoptosis in cancer cells. Among them, one of the quinolinequinones, named as 6-anilino-5, 8-quinolinequinone, LY83583 has the ability to inhibit the growth of cancer cells as an inhibitor of cyclase. The biological potential of all synthesized compounds as the analogs of the identified lead molecule LY83583 that possessed the antiproliferative efficiency was determined. The two series of the LY83583 analogs containing electron-withdrawing or electron-donating group(s) were synthesized and subsequently in vitro evaluated for their cytotoxic activity against K562, Jurkat, MT-2, and HeLa cell lines using MTT assay. All the LY83583 analogs showed antiproliferative activity with good IC50 values (less than positive control imatinib). Four analogs from each series were also selected for the determination of selectivity against human peripheral blood mononuclear cells (PBMCs). The analog AQQ15 showed high potency towards all cancer cell lines with almost similar selectivity of imatinib. In order to get a better insight into cytotoxic effects of the analog AQQ15 in K562 cells, further apoptotic effects due to annexin V/ethidium homodimer III staining, ABL1 kinase inhibition, and DNA cleaving ability were examined. The analog AQQ15 induced apoptotic cell death in K562 cells with 34.6% compared to imatinib (6.5%). This analog showed no considerable ABL1 kinase inhibitory activity but significant DNA cleavage activity indicating DNA fragmentation-induced apoptosis. Besides, molecular docking studies revealed that the analog AQQ15 established proper interactions with the deoxyribose sugar attached with the nucleobases adenine and guanidine respectively, in the minor groove of the double helix of DNA. In silico predicted pharmacokinetic parameters of this analog were found to comply with the standard range making it an efficient anticancer drug candidate for further research. Graphical abstract: Image 1 Highlights: A series of Quinolinequinone analogs (AQQ1-19 ) were designed and synthesized. The analog AQQ15 showed high potency against K562 CML cell line. The analog AQQ15 induced apoptotic cell death in K562 cells. Molecular docking study was carried out to explore the binding of AQQ15 with DNA. Pharmacokinetic properties of all analogs were in silico determined.